Cell-based Regeneration of Intervertebral Disc Defects: Review & Concepts - Freimark, Denise; Czermak, Peter (My University, 2010)
During the last century low back pain has been emerged as a widespread disease often caused by intervertebral disc degeneration (IDD). IDD in turn is a complex problem, in which a variety of causes play a crucial role. As IDD causes high costs, a corporate interest leads to a number of therapies developed. Today, these therapies focus on the restoration of the IVD function and not only on minimizing the pain caused by this disease. These approaches are often biological and aim to stimulate the regeneration of the intervertebral disc by injection of activator proteins, biomaterials, different cell types or complex cell-matrix-composites. Furthermore, the genetic engineering of disc cells and the in vitro tissue engineering offer a possibility for curing IDD. This article gives an overview on the concepts mentioned above.
Keywords: Intervertebral disc regeneration; Cell transplantation; Mesenchymal stem cell